2016
DOI: 10.1017/s1755691017000329
|View full text |Cite
|
Sign up to set email alerts
|

Earwigs (Dermaptera) from the Mesozoic of England and Australia, described from isolated tegmina, including the first species to be named from the Triassic

Abstract: Dermaptera (earwigs) are described from the Triassic of Australia and England, and from the Jurassic and Cretaceous of England. Phanerogramma heeri (Giebel) is transferred from Coleoptera and it and Brevicula gradus Whalley are re-described. The earwigs (Insecta: Dermaptera) form a relatively small, easily recognisable order. They are elongate and dorsoventrally flattened with short leathery forewings (tegmina), which cover only the most anterior part of the abdomen. They look superficially similar to staphyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…The literature for the stratigraphy of the insect bearing horizons is equally outdated and so we aim to update the ages of these historical localities to current geological nomenclature. The Rhaetian localities of Brown's Wood, Warwickshire and Apperley, Forthampton, and Wainlode Cliff (Gloucestershire) along with the Hettangian localities of Binton (Warwickshire) and Copt Heath (Birmingham) and the Toarcian locality of Strawberry Bank, Ilminster (Somerset), were previously discussed [35]. The Rhaetian localities of Aust Cliff and Brockeridge (Gloucestershire) and the Sinemurian locality of Monmouth Beach, Lyme Regis (Dorset) were also previously discussed [36].…”
Section: Localities and Agesmentioning
confidence: 97%
“…The literature for the stratigraphy of the insect bearing horizons is equally outdated and so we aim to update the ages of these historical localities to current geological nomenclature. The Rhaetian localities of Brown's Wood, Warwickshire and Apperley, Forthampton, and Wainlode Cliff (Gloucestershire) along with the Hettangian localities of Binton (Warwickshire) and Copt Heath (Birmingham) and the Toarcian locality of Strawberry Bank, Ilminster (Somerset), were previously discussed [35]. The Rhaetian localities of Aust Cliff and Brockeridge (Gloucestershire) and the Sinemurian locality of Monmouth Beach, Lyme Regis (Dorset) were also previously discussed [36].…”
Section: Localities and Agesmentioning
confidence: 97%
“…The Denmark Hill fossils he retained personally which are now held in the NHMUK were listed in his records as his "G", "D" and "S" Collections: "G" was the original Simmonds Collection of 7 specimens and two counterparts (although how and why these came into Dunstan's personal possession is not clear); "D" was the collection (numbered 1-367) that mirrored the official GSQ holdings, made up of parts or counterparts, including many types and type counterparts, plus some additional specimens; "S" was his Supplementary Collection (numbered 1-642, but including blank numbers) of additional uncited but identified specimens, plus some unidentified items. Also included was a separate group of 145 fragments, some of which have since proved valuable: Kelly et al (2018) described new dermapterans from two such fragments held at NHMUK.…”
Section: The Dunstan Registersmentioning
confidence: 99%
“…The tables, organised by insect order, follow the arrangement set out in Jell (2004), except for the addition of Dermaptera in recognition of work by Kelly et al (2018). Within each order, the described species are arranged alphabetically, as an easy finding aid.…”
Section: Where Are They Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…The Late Triassic material was collected from bed 18 of the Penarth Group at the historical locality of Strensham in the county of Worcestershire (Brodie, 1845) and was updated to current geological nomenclature by Kelly et al (2017) who found the horizon to lie within the Lilstock Formation, Cotham Member, which is Rhaetian in age. The Early Jurassic fossils were collected from three localities Binton in the county of Warwickshire, another historical locality, exposed several insect-bearing horizons, which Brodie (1845) originally described and Kelly et al (2018) found to correspond to the Planorbis Chronozone (Blue Lias Formation, Wilmcote Limestone Member) of the Hettangian. The other two localities—Stonebarrow and Catherston Lane—are very similar and are found at or near the Dorset coast.…”
Section: Geological Settingmentioning
confidence: 99%